Selective reduction in trabecular volumetric bone mineral density during treatment for childhood acute lymphoblastic leukemia - Kohler, J; Moon, R; Sands, R; Doherty, L; Taylor, P; Cooper, C; Dennison, E; Davies, J (2012)
During treatment of childhood acute lymphoblastic leukemia (ALL) fracture incidence is increased. Studies using DXA, which measures a composite of both trabecular and cortical BMD, have shown reduced BMD during treatment. We investigated changes in compartmental (cortical and trabecular) volumetric BMD (vBMD) and bone geometry using peripheral quantitative computed tomography. These outcomes were also analysed in relation to adiposity and treatment factors. Thirty nine patients with ALL (64% male, median age 7.2years (4.1-16.9)) were compared to 34 healthy controls (50% male, median age 9.1years (4.4-18.7)). DXA-derived age-specific standard deviation scores (SDS) of the lumbar spine (LS) and femoral neck (FN) were reduced in subjects with ALL compared to controls (p≤0.01). This persisted following adjustment for body size using height-specific SDS (LS -0.72±1.02 vs -0.18±0.72, p=0.01; FN -1.53±0.96 vs -0.74±0.74, p=0.001) and bone mineral apparent density (BMAD) SDS (LS -0.76±1.14 vs 0.04±1.08, p=0.01; FN -1.63±1.38 vs -0.16±1.20, p<0.001). Radial and tibial trabecular vBMD was also reduced (196.5±54.9mg/cm3 vs 215.2±39.9mg/cm3, p=0.03 and 232.8±60.3mg/cm3 vs 267.5±60.2mg/cm3, p=0.002, respectively), but cortical vBMD at the radius and tibia was similar in patients and controls. A lowered tibial bone strength index (BSI) was identified in patients with ALL (53.9±23.1mg/mm4 vs 82.5±27.8mg/mm4, p<0.001) suggesting lower fracture threshold from compressive forces. No relationships with measures of adiposity, duration of treatment or cumulative corticosteroid dose were identified. Our findings therefore suggest that reduction in trabecular vBMD during childhood ALL treatment may contribute to the observed increased fracture incidence and bony morbidity in this group. © 2012 Elsevier Inc.